Democracy on the road : a 25 year journey through India - Sharma, Ruchir Sharma (Penguind Allen Lane, 2019)
"On the eve of a landmark general election, Ruchir Sharma offers an unrivaled portrait of how India and its democracy work, drawn from his two decades on the road chasing election campaigns across every major state, travelling the equivalent of a lap around the earth. Democracy on the Road takes readers on a rollicking ride with Ruchir and his band of highly-informed fellow writers as they talk to farmers, shopkeepers and CEOs from Rajasthan to Tamil Nadu, and interview leaders from Narendra Modi to Rahul Gandhi. No other book has taken readers so close to the action, or traced the arc of modern Indian politics so immediately. Offering an intimate view inside the lives and minds of India's political giants and its people, Sharma explains how the complex forces of family, caste and community, economics and development, money and corruption, Bollywood and Godmen, have conspired to elect and topple Indian leaders since Indira Gandhi. The ultimately encouraging message of Ruchir's travels is that, while democracy is retreating in many parts of the world, it is thriving in India"--Dust jacket flap.